Cyber wars: Catholics for a free choice and the online abortion debate - Bloch, Jon P. (Review of Religious Research, 2007)
Catholics for a Free Choice (CFFC) performs considerable advocacy online, through its website as well as through press releases and interviews that appear at other sites. Opponents to CFFC also frequently post online. This article analyzes this online debate to explore how it is conceptually framed. CFFC presents a discourse that is promoted as finding ideological consistency between Catholic values and being prochoice, and which addresses a greater social good beyond the Church per se. In making these self-referential claims, CFFC could be viewed as a “community of discourse” (Wuthnow 1989) that reckons with “problems of articulation” by dealing with both specific and broader tensions. Online opponents to CFFC likewise could be viewed as communities of discourse that promote themselves as having the true Catholic values that serve the greater good. On balance, CFFC online would seem to reflect the larger quandaries of abortion discourse, whereby the Internet can offer a representative depiction of democratic free speech articulated on this controversial issue. Yet at the same time, there is little evidence to date that this online debate is changing anyone's mind or building a new consensus, despite some efforts on the part of CFFC to do so.
Keywords: dept.soc; ⛔ No DOI found